2005
DOI: 10.1227/01.neu.0000146210.13318.e8
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Central Nervous System Hemophagocytic Lymphohistiocytosis: Case Report

Abstract: Radiotherapy with corticosteroid administration led to a complete resolution of the lesions, although for only a transitory remission. Although HLH is extremely rare, the existence of this disease isolated in the CNS should be documented, and further case accumulation and therapeutic investigations are needed to clarify the pathophysiological characteristics of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 8 publications
0
24
1
Order By: Relevance
“…Most previous studies of MRI lesions in patients with HLH consisted of either case series 8,19,20 or case reports, 9,12,[21][22][23][24][25] with no common analysis of MRI and sometimes including patients with CT scans, evaluated children at an older age (median age of 6 months, 13 9 months, 11 and 5 years 19 ), or including both primary and secondary causes of HLH. Although the brain MRI selection criteria (brain MRI less than 6 months) in this study could have induced a bias toward children with clinically suspected CNS involvement, we have observed that initial abnormal neuroradiologic findings at the onset of primary HLH appeared to be relatively infrequent, with 67% of children having a normal cerebral MRI scan at onset (the actual percentage probably could be higher if we also take into account the children who did not undergo MRI during the first 6 months).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies of MRI lesions in patients with HLH consisted of either case series 8,19,20 or case reports, 9,12,[21][22][23][24][25] with no common analysis of MRI and sometimes including patients with CT scans, evaluated children at an older age (median age of 6 months, 13 9 months, 11 and 5 years 19 ), or including both primary and secondary causes of HLH. Although the brain MRI selection criteria (brain MRI less than 6 months) in this study could have induced a bias toward children with clinically suspected CNS involvement, we have observed that initial abnormal neuroradiologic findings at the onset of primary HLH appeared to be relatively infrequent, with 67% of children having a normal cerebral MRI scan at onset (the actual percentage probably could be higher if we also take into account the children who did not undergo MRI during the first 6 months).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, isolated CNS involvement, either preceding systemic symptoms or remaining the only manifestation, may present a formidable diagnostic challenge [22,40,66,106].…”
Section: Why Hlh Is Still Overlookedmentioning
confidence: 99%
“…In more severe involvement, infiltration extends into the perivascular spaces. In advanced stages, massive tissue infiltration may follow, particularly affecting the white matter, and may result in perifocal gliosis, areas of necrosis and demyelination [2,6]. Shinoda et al has reported a case of HLH limited to CNS without the involvement of other systemic organs or inflammatory response [6].…”
Section: Discussionmentioning
confidence: 99%